2017
DOI: 10.1002/hep4.1035
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir‐based regimens for the treatment of chronic hepatitis C in severe renal dysfunction

Abstract: Sofosbuvir (SOF) is a nonstructural 5B polymerase inhibitor with activity in all hepatitis C virus (HCV) genotypes and is the backbone of many anti‐HCV drug regimens. SOF is converted into inactive metabolites that undergo renal excretion. Patients with an estimated glomerular filtration rate (eGFR) < 30 mL/minute/1.73 m2 may experience increased drug exposure and thus potential toxicities along with decreased efficacy due to dose reduction or drug discontinuation. This is a single‐center study evaluating safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 27 publications
2
31
0
3
Order By: Relevance
“…This high SVR rate may be related to the observation that SOF produces similar concentrations of active intracellular metabolites independent of renal function . Similarly, high SVR rates were reported by Cox‐North et al who studied the safety and effectiveness of full dose SOF in 29 patients with severe renal dysfunction . Borgia et al also reported a high SVR rate of 95% in his phase II study on 59 patients with chronic HCV and ESRD undergoing haemodialysis or peritoneal dialysis who received open‐label full dose sofosbuvir/velpatasvir for 12 weeks .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This high SVR rate may be related to the observation that SOF produces similar concentrations of active intracellular metabolites independent of renal function . Similarly, high SVR rates were reported by Cox‐North et al who studied the safety and effectiveness of full dose SOF in 29 patients with severe renal dysfunction . Borgia et al also reported a high SVR rate of 95% in his phase II study on 59 patients with chronic HCV and ESRD undergoing haemodialysis or peritoneal dialysis who received open‐label full dose sofosbuvir/velpatasvir for 12 weeks .…”
Section: Discussionmentioning
confidence: 62%
“…In real‐life experience, there are reports of deterioration of renal function on SOF‐based therapy . On the other hand, several studies have demonstrated the safety of sofosbuvir in patients with severe CKD …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of anti-HCV PI drugs, boceprevir, and telaprevir in coinfected persons seems to illustrate a greater antiviral efficacy within the HIV/HCV coinfected population [43]. Different combination regimens reduce the risk of liver-related complications, sustained virological rates between 27% and 44% [5,44]. There is no cure for the HIV which causes AIDS, but a combination of drugs can keep the virus away from replicating and damaging the immune system [33].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Another analysis reported the results of patients with eGFR <30 mL/min/1.7 m 2 who received SOF. All patients completed treatment, 97% achieved SVR, with 90% having unchanged renal function, four patients had improved renal function, with two discontinuing haemodialysis …”
mentioning
confidence: 98%